Low validity of self-report in identifying recent mental health diagnosis among U.S. service members completing Pre-Deployment Health Assessment (PreDHA) and deployed to Afghanistan, 2007: a retrospective cohort study - Nevin Remington L (BMC, 2009)
Abstract Background Since 1998, the U.S. Armed Forces has used the mandatory Pre-Deployment Health Assessment (PreDHA) screening questionnaire as a means of assessing the health and suitability of U.S. service members for deployment. Limited data exists to quantify the validity of the self-reported PreDHA. This study was conducted to assess the validity of self-reporting in PreDHA to identify deployed service members who have had a recent mental health disorder diagnosis. Methods A retrospective cohort study was conducted on 15,195 U.S. service members deployed in support of combat and reconstruction operations in Afghanistan. The Defense Medical Surveillance System (DMSS), the DoD's longitudinal medical surveillance database, was queried to identify cases among the cohort with a recent diagnosis of a pertinent mental health disorder and to obtain those subjects' responses to the PreDHA. Results Of the study cohort, 11,179 (73.6%) subjects had a PreDHA available within the DMSS at the time of analysis. A total of 615 subjects (4.0%) had one or more mental health disorder diagnoses during the pre-deployment period. Out the 615 subjects with diagnosed mental health disorders, 465 had a PreDHA. Among these, only 224, not quite half, answered in the affirmative to the PreDHA question: "During the past year, have you sought counseling or care for your mental health?" Conclusion This study demonstrates that the self-reported PreDHA has low validity for identifying service members with diagnosed mental health disorders. The development of electronic decision-support systems which automatically screen electronic health records to identify high-risk service members may prove a valuable component of improved pre-deployment screening processes.